The Effect of Lactiplantibacillus plantarum x3-2b Bacterial Powder on the Physicochemical Quality and Biogenic Amines of Fermented Lamb Jerky - Xiaotong Li; Guanhua Hu; Xueying Sun; Erke Sun; Yue Zhang; Yancheng Zhong; Lin Su; Ye Jin; Fan Yang; Lihua Zhao (Foods, 2023)
In this study, a protective agent was added to prepare a high-activity Lactiplantibacillus plantarum x3-2b bacterial powder as a fermentation agent and explore its effect on the physicochemical quality, biogenic amines, and flavor of fermented lamb jerky. A composite protective agent, composed of 15% skim milk powder and 10% trehalose, was used, and bacterial mud was mixed with the protective agent at a 1:1.2 mass ratio. The resulting freeze-dried bacterial powder achieved a viable count of 5.1 lg CFU/g with a lyophilization survival rate of 87.58%. Scanning electron microscopy revealed enhanced cell coverage by the composite protective agent, maintaining the cell membrane’s integrity. Inoculation with x3-2b bacterial powder increased the pH and the reduction in aw, enhanced the appearance and texture of fermented lamb jerky, increased the variety and quantity of flavor compounds, and reduced the accumulation of biogenic amines (phenethylamine, histamine, and putrescine). This research provides a theoretical basis for improving and regulating the quality of lamb jerky and establishes a foundation for the development of bacterial powder for the commercial fermentation of meat products.